Origins, Development, Current Challenges and Future Directions with Activated Prothrombin Complex Concentrate for the Treatment of Patients with Congenital Haemophilia with Inhibitors - Brackmann, Hans H.; Schramm, Wolfgang; Oldenburg, Johannes; Cano, Viridiana; Turecek, Peter L.; Négrier, Claude (Hämostaseologie, 2020)
Congenital haemophilia A (HA) is caused by deficiency of coagulation factor VIII (FVIII) activity, leading to spontaneous or traumatic bleeding events. While FVIII replacement therapy can treat and prevent bleeds, approximately 30% of patients with severe HA develop inhibitor antibodies that render FVIII replacement therapy ineffective. The bypassing agents (BPAs), activated prothrombin complex concentrate (aPCC) and recombinant activated FVII, first approved in 1977 and 1996, respectively, act to generate thrombin independent of pathways that involve factors IX and VIII. Both may be used in patients with congenital haemophilia and inhibitors (PwHIs) for the treatment and prevention of acute bleeds and quickly became standard of care. However, individual patients respond differently to different agents. While both agents are approved for on-demand treatment and perioperative management for patients with congenital haemophilia with inhibitors, aPCC is currently the only BPA approved worldwide for prophylaxis in PwHI. Non-factor therapies (NFTs) have a mechanism of action distinct from BPAs and have reported higher efficacy rates as prophylactic regimens. Nonetheless, treatment challenges remain with NFTs, particularly regarding the potential for synergistic action on thrombin generation with concomitant use of other haemostatic agents, such as BPAs, for the treatment of breakthrough bleeds and in perioperative management. Concomitant use of NFTs with other haemostatic agents could increase the risk of adverse events such as thromboembolic events or thrombotic microangiopathy. This review focuses on the origins, development and on-going role of aPCC in the evolving treatment landscape in the management of PwHI.
Keywords: congenital haemophilia; inhibitors; bypassing agents; FEIBA; aPCC